New results on landscape boundaries - Mezősi, Gábor; Bata, Teodóra (Acta Geographica Debrecina Landscape & Environment series, 2011)
The correct delineation of geographical and landscape ecological units, being the fundamental territorial domains of both physical and human geography, is very important from the aspect of several other related disciplines as well. It is hard to tell how distinct landscape units, or landscape ecological units can be, from a statistical point of view. The present study investigates how welldefined (definable) geographical units (landscapes, landscape types) are in a statistical and mathematical sense. Since landscape forming factors do not exhibit distinct boundaries either, during the analysis it is better to consider them as ecotones. Integration of factors, and the unclear interpretation of present landscape boundaries do further complicate the sound mathematical evaluation of the studied geographical units. In order to resolve these problem GIS techniques were applied.